Abu Tbeirah’s Craft Area NE: A Preliminary Survey - D’Agostino, Franco; Romano, Licia (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Tell Abu Tbeirah (or Tubairah) is divided in four sectors by a pipeline running South to North and by the depression of an old canal running from South-East to North-West (Figure 1). While the Southern part of the site has been almost untouched by modern activities, the Northern part suffered of several anthropic actions connected both with war events and with the exploitation of the soil for industrial and civil purposes. No traces of looting on the site have been so far detected.